An implementation and analysis of deep learning models for the detection of wheat diseases - Zubair, Ahmad; Keya, Sharmin Akter; Shailee, Tasnia Zarin; Lenin, Syed Mahathir Md; Nandi, Dhruba (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2023.